Heterogenous effect of industrialisation on environmental degradation in Southern African Customs Union (SACU) countries: Quantile analysis - Teboho Jeremiah Mosikari (Economies, 2023)
Southern African Customs Union (SACU) countries are under pressure to commit themselves to sustainable environmental activities. This study employed data from 2007 to 2021 using quantile regression to determine the heterogenous effects of industrialisation on environmental degradation in SACU countries. Prior to the main results, this study investigated and confirmed the existence of a long-run relationship between industrialisation and environmental degradation. This study confirms the heterogeneous effect of industrialisation on environmental degradation. The results through quantile process estimates demonstrated an inverted U-shaped curve. The inverted U-shape suggests that industrialisation at lower and higher quantiles has a minor effect on the environment compared to medium quantiles, where it has a higher effect. This study found that industrialisation increases environmental degradation in the 4th to 6th quantiles, whereas in the 7th to 8th quantiles, industrialisation reduces environmental degradation. Therefore, it is recommended by this study that to mitigate environmental degradation, firms in SACU countries are encouraged to adopt environment-friendly technologies in their production.
Keywords: 330; industrialisation; environmental degradation; SACU; panel quantile regression